Assessing the Efficacy of Ultrasound-Guided Erector Spinae Plane Block in Pyelolithotomy or Nephrectomy Patients : Ultrasound-Guided Erector Spinae Plane Block in Pyelolithotomy or Nephrectomy - Tariq, Sumayya; Nayyar, Shaheer; Ashfaq, Shumaila; Zeb, Anum; Ahmad, Hafiz Naseer; Arshad, Maria (Pakistan Journal of Health Sciences, 2025)
Nephrectomy and pyelolithotomy are invasive surgical procedures often associated with significant postoperative pain, necessitating effective analgesia for optimal recovery. Objectives: To evaluate the efficacy of ultrasound-guided erector spinae plane block (ESPB) in patients undergoing nephrectomy or pyelolithotomy, with a focus on pain relief, dermatome coverage, and duration of analgesia. Method: This quasi-experimental study was conducted over 12 months in the Anesthesia Department of Sharif Medical City Hospital, Lahore, enrolling 66 patients. After receiving ESPB, postoperative pain was assessed using the Visual Analogue Scale (VAS) at rest, where 0 indicated no pain and 10 indicated the worst possible pain. Dermatomal coverage was evaluated via pinprick testing, and the time to first rescue analgesia was recorded. Data analysis was performed using SPSS version 25.0. Results: Out of the 66 patients, 47 were male and 19 female. VAS scores showed a significant reduction from 2.98 ± 1.31 at 24 hours to 0.87 ± 0.83 at 72 hours (p=0.000). Pain on movement significantly decreased (p=0.000), while sleep quality showed no significant improvement. The proportion of patients reporting adequate pain relief rose from 67.3% at 24 hours to 81.5% at 72 hours (p=0.000). Peak rescue analgesia demand occurred at 15–16 hours postoperatively (25 patients), indicating prolonged initial analgesia. Conclusions: It was concluded that the ultrasound-guided erector spinae plane block (ESPB) effectively manages pain, significantly reducing VAS scores over 72 hours. This method delivers high-quality analgesia with consistent dermatome coverage following pyelolithotomy and nephrectomy.